Green Economy Towards Sustainable Tourism Development in Indonesia - Widayanto, Aditya Dwi Ramadhan; Nurrahma, Aisyah Asri (Proceedings of International Conference of Graduate School on Sustainability, 2023)
Green economy development strategies and the transition from conventional economic development models to a green economy have become necessary due to the negative impact of conventional economic development models on the local and global environment. Indonesia has been implementing this concept for a long time, known as â€œRencana Pembangunan Jangka Menengah Nasionalâ€. The tourism industry in Indonesia is one of the industries that give 4,8% of the GDP and the second highest source of foreign exchange after the oil and gas sector. During the pandemic COVID-19 crisis, it is the best time to re-thinking tourism to keep this industry sustainable. The purpose of this study is to explain the implementation of a green economy towards sustainable development and sustainable tourism in Indonesia. The research method used in this study is qualitative using descriptive analysis to make a specific, structured, accurate, and actual picture of the phenomena occurring in the study. The data collection technique used is documentation from various sources and literature reviews from various credible journals, various regulations in the form of laws, presidential regulations, Ministerial regulations, and policies launched by the central government related to the green economy and sustainable tourism. The result of the research shows that the implementation of the green economy in Indonesia has good progress toward sustainable development and sustainable tourism. There is 3 point strategy towards sustainable tourism which are Sustainable Tourism Destination (STD), Sustainable Tourism Observation (STO), and Sustainable Tourism Certification (STC).